Large-scale production and efficient recovery of PHB with desirable material properties, from the newly characterised Bacillus cereus SPV - Boccaccini, Aldo R.; et al. (Journal of Biotechnology, 2007)
A newly characterised Bacillus strain, Bacillus cereus SPV was found to produce PHB at a concentration of 38% of its dry cell weight in shaken flask cultures, using glucose as the main carbon source. Polymer production was then scaled up to 20 L batch fermentations where 29% dry cell weight of PHB was obtained within 48 h. Following this, a simple glucose feeding strategy was developed and the cells accumulated 38% dry cell weight of PHB, an increase in the overall volumetric yield by 31% compared to the batch fermentation. Sporulation is the cause of low PHB productivity from the genus Bacillus [Wu, Q., Huang, H., Hu, G.H., Chen, J., Ho, K.P., Chen, G.Q., 2001. Production of poly-3-hydroxybutyrate by Bacillus sp. JMa5 cultivated in molasses media. Antonie van Leeuwenhoek 80, 111-118]. However, in this study, acidic pH conditions (4.5-5.8) completely suppress sporulation, in accordance with Kominek and Halvorson [Kominek, L.A., Halvorson, H.O., 1965. Metabolism of poly-β-hydroxybutyrate and acetoin in Bacillus cereus. J. Bacteriol. 90, 1251-1259], and result in an increase in the yield of PHB production. This observation emphasises the potential of the use of Bacillus in the commercial production of PHB and other PHAs. The recovery of the PHB produced was optimised and the isolated polymer characterised to identify its material properties. The polymer extracted, was found to have similar molecular weight, polydispersity index and lower crystallinity index than others reported in literature. Also, the extracted polymer was found to have desirable material properties for potential tissue engineering applications. © 2007 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.larges
Keywords: Bacillus cereus SPV; Crystallinity index; Fermentation; Polydispersity index; Polyhydroxybutyrate; Polymer extraction